2021
DOI: 10.7146/sjsep.v3i.128317
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Meta-Study of a Decade of the Holistic Ecological Approach to Talent Development

Abstract: The Holistic-Ecological Approach (HEA) was introduced in 2010, and it is now important to provide a critical review after a decade of research elaborating on the framework. The purpose of this study was to critically assess the methodological and theoretical trends in research using the HEA in the study of athletic talent development environments (ATDE). We used a qualitative meta-study to review twelve studies published from 2010 to the first quarter of 2021. Our meta-theory analysis found that future studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
(138 reference statements)
0
15
0
Order By: Relevance
“…The Athlete Talent Development Environment (ATDE: (1)) was used as a framework for data collection and organisation. Acknowledging Feddersen and colleagues’ (2021) ( 26 ) work on the limitations of the ATDE, we extended its use, emphasising the ecological level of analysis by embracing a Gibsonian perspective ( 9 ), with particular emphasis on ( 17 ) relational view of affordances in the SIF. Here, affordances are not just passively situated in isolation in the materiality of immediate behavioral settings of a sports organisation (training session, competition), but are entwined in a particular way of life ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Athlete Talent Development Environment (ATDE: (1)) was used as a framework for data collection and organisation. Acknowledging Feddersen and colleagues’ (2021) ( 26 ) work on the limitations of the ATDE, we extended its use, emphasising the ecological level of analysis by embracing a Gibsonian perspective ( 9 ), with particular emphasis on ( 17 ) relational view of affordances in the SIF. Here, affordances are not just passively situated in isolation in the materiality of immediate behavioral settings of a sports organisation (training session, competition), but are entwined in a particular way of life ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, intentionality in the sense of value-directedness characterizes environmental structures [i.e., a form of life/ATDE] and processes [i.e., sports training methods] as much as it does the organisms [football players] who shape and are shaped [e.g., skill development] by those structures and processes. This implies that values are necessary constraints on both the constitution and the selection of affordances [( 26 ) text in brackets added)]…”
Section: Introductionmentioning
confidence: 99%
“…In Scotland, Martindale and colleagues ( 7 ) developed a survey that could assess the quality of an athletic talent development environment (ATDE), and in Denmark, Henriksen and colleagues completed a series of innovative in-depth case studies of successful ATDEs in Scandinavia ( 8 , 9 , 10 ). Today, the ecology of talent development discourse has matured, as visible in two recent reviews summarising key findings of more than a decade of ecological talent development research and related practice ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of the studies, the authors focused on positive (wellbeing, long-term athletic and personal development) and less positive (illbeing, limited athletic and personal development) talent development outcomes and related functional and dysfunctional features of ATDEs . Such an explicitly holistic definition of environment success is a welcome addition to the original literature that defined success as a track record of developing elite athletes but found that successful environment did in fact promote holistic development ( 11 ). The features were further sorted into four categories with clear connections to the ESF model (see Figure 2 and Table 1 ): preconditions, organisational culture, integration of efforts and quality holistic preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Such TDEs are worthwhile studying from a performance perspective to identify features supportive of athletic FUNCTIONAL AND DYSFUNCTIONAL FEATURES WITHIN TDEs 3 development within and across sports and countries. Indeed, sport psychology research has frequently embraced this approach within the past (Feddersen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%